Peningkatan Hasil Belajar IPS Menggunakan Model Cooperative Learning Tipe Script di Kelas VI SD - Afriadi, Nila Sari; Nasrul, Nasrul; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was improve the students achievement in learning social science usedScript of 6th grade elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were students of 6th grade were 20 people consist of 12 men and 8 women. Research conducted in two cycles with research procedure includes of planning, implementation, observation, and reflection. The result of research was improve a) Lesson plan the cycles of I was 78,57% and the cycles II of 92,86% b) Implementation teacher’s activity of I cycle was 76,38% and II cycle was 94,44% while implementation students activity of I cycle was 72,21% and II cycle was 91,66% c) the students learning outcomes in the I cycle was 77 and II cycle was 86,41. It can be concluded that used Script model can improve students achievement in learning social science of 6th grade at SDNegeri 10 Surau Gadang Padang.Keyword : Learning outcomes, Social science, Script